Conflict Management and Interdisciplinary History. Presentation of a New Project and an Analytical Model - Wubs-Mrozewicz, Justyna (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This article advances the idea that the concept of conflict resolution, which is usual in social, economic, political and legal history of premodern Europe and in the social sciences in general, is too goal-oriented and therefore unsatisfactory for the analyses of conflicts. Instead, a problem-oriented concept of conflict management is proposed. It consists of prevention, provocation, maintenance of the status quo, escalation and de-escalation, as well as resolution. Such a concept allows to analyse multi-level conflicts (individual, group, large-scale) pertaining diverse yet interrelated issues. This article shows how it will be used to analyse contentious issues which are related to mercantile cities in premodern cities in northern Europe (1350-1570), in a recently granted NWO VIDI project.